Changes in Rural Poverty Among Occupational Groups in Odisha: An Analysis of Post-Reform Period. (July 2020) - Sahoo, Priyabrata; Sahoo, Dibakar; Chandra, Subhash
Abstract: This article is an attempt to study the changes in rural poverty and its link with growth of farm sector output for Odisha in the post-reform period. The rural household-type (occupational groups) classification of National Sample Survey Organisation (NSSO) from the unit-level data of Consumer Expenditure Survey (CES) has been used for the class analysis of rural poverty. The Odisha economy has recorded high growth in net state domestic product (NSDP) in the post-reform period. During the decade of the 1990s, the state witnessed a negative growth in farm output, lower reduction in rural poverty and distress occupational mobility from farm to non-farm sector. However, in the next decade, the farm sector registered high growth, higher rural poverty reduction and occupational mobility within the farm sector. There has also been higher growth in monthly per capita expenditure (MPCE) and faster reduction in rural poverty among all the rural occupational groups in the decade of the 2000s. Thus, it is the growth of the farm sector, which remains the major driver of rural poverty reduction in Odisha.